Performance analysis of cooperative wireless sensor network with index‐based modulation. Issue 5 (29th March 2019) - Neelamegam, Subhashini; Mahalingam, Murugan
Abstract : Spatial modulation (SM) emerges as a potential technique for next generation wireless networks. Enhanced spectral efficiency and equitable system complexity led SM to various innovations. In SM only one radio‐frequency chain is active during the transmission of the signal. The information is carried by the index of the active antenna. Throughput loss and reduced spectrum utility of higher‐order modulation schemes can be overcome by activating more than one antenna. The shortcoming of SM is overcome by an enhanced SM in which index of an antenna and its constellation conveys the information. In the proposed wireless sensor network nodes are considered with two antennas. Based on the primary constellation the symbols are transmitted from a single active antenna and symbols from secondary constellation are transmitted from the two active antennas. The performance of the proposed network is compared to the network with SM.